2006
DOI: 10.1063/1.2184529
|View full text |Cite
|
Sign up to set email alerts
|

Health Monitoring of Rock Bolts Using Ultrasonic Guided Waves

Abstract: It is necessary to quantify the amount of delamination present in load bearing rock bolts, as small amounts may be deemed acceptable and large amounts may lead to catastrophic failure. In this work, a semi-analytical FEM model is used to calculate the theoretical wave structures for a rod embedded in concrete. A qualitative relationship between percent delamination and wave reflection energy is demonstrated. It is shown that with the proper selection of inspection parameters, it is possible to inspect large le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Na et al [8,14,15] utilized the guided waves for the inspection of steel-concrete interfaces and glass fiber polymer-concrete interfaces. Ervin et al [16,17] used both low (<200 kHz) and high (2)(3)(4)(5)(6)(7)(8)(9) guided longitudinal modes to ultrasonically monitor the accelerated corrosion experiments. It was found that some modes were sensitive to the combined effect of bond deterioration and mortar stiffness reduction while some other modes related well to change in crosssectional area.…”
Section: Introductionmentioning
confidence: 99%
“…Na et al [8,14,15] utilized the guided waves for the inspection of steel-concrete interfaces and glass fiber polymer-concrete interfaces. Ervin et al [16,17] used both low (<200 kHz) and high (2)(3)(4)(5)(6)(7)(8)(9) guided longitudinal modes to ultrasonically monitor the accelerated corrosion experiments. It was found that some modes were sensitive to the combined effect of bond deterioration and mortar stiffness reduction while some other modes related well to change in crosssectional area.…”
Section: Introductionmentioning
confidence: 99%
“…If these cracks are closed and hence poor reflectors, then nonlinear methods must be incorporated under the constraints imposed by guided-wave propagation in the element (Pruell 2009;Jhang 2000). A number of investigators have covered rod-guided waves with the intent of solving problems such as rebar corrosion in concrete, rock anchor-bolt bonding, and utility pole, guidewire anchor corrosion in soils (Beard 2003;Erwin et al 2009;Yang and Yu 2006;He et al 2006 ). In general, these three specific applications need high sensitivity at the rod surface and therefore benefit from narrow-band, guided-wave modes such as low-order longitudinal or torsional modes that result in relatively higher levels of acoustical energy at or near the rod's surface.…”
Section: Approachmentioning
confidence: 99%
“…They also selected a high surface interface sensitive mode such as the L(0,1)'s low attenuation point around 100 kHz to detect progressive debonding between grout and steel due to corrosion. He et al (2006) performed similar guided wave measurements for rock-bolt debonding localization and characterization at distances up to 10 ft.…”
Section: Defect Detectionmentioning
confidence: 99%